PERANCANGAN KAMPANYE SOSIAL WONG JAWA ILANG JAWANE UPAYA MELESTARIKAN BUDAYA JAWA DI YOGYAKARTA - Agust Pratama Hendra Kusuma Harta S1 (Saraswati)
In this modern era, development of technology doesn’t come together with positive foreign culture. And nowadays, any foreign culture can come without filtering. However, it cannot be denied that local ethics and positive manners are still needed, especially when socializing with other people. The prominent evident of the lack of Javanese ethics and manners is only few people say “Excuse me” or “Nderek langkung” when passing elder people. Even the youngsters are too lazy to bow their heads when passing elders. The social campaign of javanese people loose their culture aimed to preserve the javanese culture in yogyakarta aims to restore the uniqueness of Javanese culture, which nowadays being forgotten. The campaign is held by projecting Mural as the outdoor medium of Visual Communication Design. This Mural is expected to communicate the main message of the campaign.Keywords : Social Campaign , javanese culture, Manners